CURRENT STATUS OF PROBLEM OF EARLY DIAGNOSIS OF OVARIAN CANCER AND ITS SOLUTIONS (LITERATURE REVIEW) - O. V. Makarov; S. A. Moshkovskiy; M. A. Karpova; M. R. Narimanova (Опухоли женской репродуктивной системы, 2015)
Ovarian cancer (OC) is one of the most common malignant tumors of the reproductive system. The five-year survival rate is extremely low. This disease is difficult to verify due to lack of pathognomonic symptoms and timely diagnosis. The key issue to increase survival in ovarian cancer is finding new methods for early diagnosis. Thus, the development of new methods for diagnosis of ovarian cancer is one of the most urgent problems in modern oncology. The basic approach in this matter is searching for new biomarkers of ovarian cancer, which will be characterized by such concepts as sensitivity and specificity. Biomarkers present in modern oncology, including CA-125, have insufficient specificity and have low sensitivity. The advantage of using a combination of several diagnostic biomarkers instead of one or panels of markers has been proved. Modern proteomic technologies such as two-dimensional electrophoresis, mass spectrometric methods are a valuable tool for finding new biomarkers for various malignancies, particularly ovarian cancer. The best results are achieved by using SELDI-TOF technology (Surface-enhanced laser desorption/ionization time-of-flight), combining the use of chromatographic protein chips with mass spectrometric detection. Serum amyloid A1 deserves the greatest attention between all of the biomarkers identified using mass spectrometric methods, as its ability to have a direct influence on the development of the tumor has been proved. Also its increase by hundreds of times during the disease has been found compared to the other candidate biomarkers identified by mass spectrometry. The main characteristics of serum amyloid 1A have been analyzed and found as one of the most promising markers for the combined determination for prompt diagnosis of ovarian cancer.